Evaluating the diagnostic efficiency of ultrasound and serum autoantibodies in Hashimoto’s thyroiditis: a cross-sectional study - Hai-Long Tan; Huan Ge; Zi-En Qin; Ya-Ling Jiang; Shi Chang; Neng Tang (Scientific Reports)
Abstract Hashimoto’s thyroiditis is the most common endocrine disorder, with diagnosis primarily relying on serum thyroid autoantibodies and ultrasound feature. However, the diagnostic accuracy of serum thyroid autoantibodies and ultrasound for Hashimoto’s thyroiditis remains unclear. This study enrolled 24,014 participants, including 6,195 (25.8%) patients diagnosed with Hashimoto’s thyroiditis. The diagnostic performance of ultrasound and serum thyroid autoantibodies was assessed against histopathological findings. Both serum thyroid autoantibodies and ultrasound demonstrated high overall specificity (91.8%, 89.8%, and 92.1%, respectively) and negative predictive value (87.4%, 86.9%, and 86.0%, respectively) for diagnosing Hashimoto’s thyroiditis. Additionally, thyroid autoantibodies level was strongly correlated with the risk of Hashimoto’s thyroiditis. However, these methods demonstrated low independent sensitivity (30.5%, 28.5%, and 22.9%, respectively) and positive predictive value (43.7%, 32.4%, and 28.5%, respectively). Furthermore, the combined use of these methods resulted in a notably low sensitivity of 33.6%, despite a relatively low false positive rate of 11.9%. Elevated thyroid autoantibodies strongly correlate with Hashimoto’s thyroiditis risk. While both autoantibodies and ultrasound demonstrate high specificity and negative predictive value, their low independent sensitivity and positive predictive value limit reliability. Combined use reduces false positives but further diminishes sensitivity.